Evidence for a biphasic mode of respiratory syncytial virus transmission in permissive HEp2 cell monolayers. Issue 1 (December 2016) - Huong, Tra; Iyer Ravi, Laxmi; Tan, Boon; Sugrue, Richard
Abstract Background During respiratory syncytial virus (RSV) infection filamentous virus particles are formed on the cell surface. Although the virus infectivity remains cell-associated, low levels of cell-free virus is detected during advanced infection. It is currently unclear if this cell-free virus infectivity is due to a low-efficiency specific cell-release mechanism, or if it arises due to mechanical breakage following virus-induced cell damage at the advanced stage of infection. Understanding the origin of this cell-free virus is a prerequisite for understanding the mechanism of RSV transmission in permissive cells. In this study we describe a detailed examination of RSV transmission in permissive HEp2 cell monolayers. Methods HEp2 cell monolayers were infected with RSV using a multiplicity of infection of 0.0002, and the course of infection monitored over 5 days. The progression of the virus infection within the cell monolayers was performed using bright-field microscopy to visualise the cell monolayer and immunofluorescence microscopy to detect virus-infected cells. The cell-associated and cell-free virus infectivity were determined by virus plaque assay, and the virus-induced cell cytotoxicity determined by measuring cell membrane permeability and cellular DNA fragmentation. Results At 2 days-post infection (dpi), large clusters of virus-infected cells could be detected indicating localised transmission in the cell monolayer, and during this stage we failed to detect either cell-free virus or cell cytotoxicity. At 3 dpi the presence of much larger infected cell clusters correlated with the begining of virus-induced changes in cell permeability. The presence of cell-free virus correlated with continued increase in cell permeability and cytotoxicity at 4 and 5 dpi. At 5 dpi extensive cell damage, syncytial formation, and increased cellular DNA fragmentation was noted. However, even at 5 dpi the cell-free virus constituted less than 1 % of the total virus infectivity. Conclusions Our data supports a model of RSV transmission that initially involves the localised cell-to-cell spread of virus particles within the HEp2 cell monolayer. However, low levels of cell free-virus infectivity was observed at the advanced stages of infection, which correlated with a general loss in cell monolayer integrity due to virus-induced cytotoxicity.